2023
DOI: 10.1007/s15010-023-02009-8
|View full text |Cite
|
Sign up to set email alerts
|

Changes in body mass index, weight, and waist-to-hip ratio over five years in HIV-positive individuals in the HIV Heart Aging Study compared to the general population

Abstract: Purpose Overweight and obesity have increased in people living with HIV (PLH). Our study evaluated weight, body-mass-index (BMI), and waist-to-hip ratio (WHR) change over 5 years of follow-up in PLH compared to the general population. Methods HIV-positive participants in the HIV Heart Aging (HIVH) study were matched 1:2 by age and sex with HIV-negative controls of the population-based Heinz Nixdorf Recall (HNR) study. Both studies were recruited in the Ger… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…This observation aligns with the findings of other observational studies, affirming a sustained increase in BMI over time in patients, regardless of their HIV status. 17 , 18 , 19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation aligns with the findings of other observational studies, affirming a sustained increase in BMI over time in patients, regardless of their HIV status. 17 , 18 , 19 …”
Section: Discussionmentioning
confidence: 99%
“…This observation aligns with the findings of other observational studies, affirming a sustained increase in BMI over time in patients, regardless of their HIV status. 17,18,19 There is ample evidence that PLWH starting INSTI gain significantly more weight compared to PLWH using a firstline ART regimen without INSTI. 10,20,21,22 However, most studies addressing weight gain in people on INSTI-based ART lack comparison with HIV-negative controls, which makes it hard to address excess weight gain compared to the non-HIV-positive population.…”
Section: Discussionmentioning
confidence: 99%
“…Contemporaneous antiretroviral therapies (ART) [3], health-related behaviors [4], and food security [5]/insecurity [6] (depending on the population), have all been implicated in the rising prevalence of obesity among PWH. In the United States, for example, PWH from the HIV Heart Aging Study (85% male) were found to have higher body mass index (BMI) increases over a 5 year period compared to matched people without HIV from the German-based Heinz Nixdorf Recall Study [7 ▪▪ ]. Further, in the US Military HIV Natural History Study (93% male, 51% White), the prevalence of overweight status at HIV diagnosis increased from 25% between 1985 and 1990 to 41% between 1996 and 2004, whereas the prevalence of obesity increased from 3% to 12%.…”
Section: Introductionmentioning
confidence: 99%